(untitled) (Global Journal of Human-Social Science, 2013)
Research shows that managing school is like managing a state So the school principal must be politician economist psychologist and sociologist Culture ethnicity gender and religion of the school population may diverse and customers of the school require satisfying their needs This paper of characteristics of effective principal discusses how perfect school principals look like There are nine self-assessment tips that principals can measure themselves I derived these nine tips from the nine alphabet letters that the word principal consists of Each alphabet letter of the common word given to school leader stands for good jobs required to be fulfilled by the principal Principals will understand that their task is unique and require extra knowledge and standards to apply it After reading books and articles wrote by different scholars I noted that leadership and principalship and are unique task that are not easy all people to engage in The principal is the corner stone of the school and plays important role on development of education programs I see that it is necessary to equip principals with knowledge and skills to interact multiple changes and complex task of managing human being Schools are the mirror of the life and birthplace of human resource so leaders of schools must be familiar with management skills and leadership styles The main objective of the schools is to produce creative leaners who will be leaders of tomorrow hence principals must be role models that students and other people in the schools will learn from them